Short Communication: Vegetation and bird diversity in Pesanggrahan's lowland tropical forest, Malang, Indonesia - FATCHUR ROHMAN; NAILUL INSANI; PURWANTO PURWANTO; AGUS DHARMAWAN; INDRA FARDHANI; FARID AKHSANI (Society for Indonesian Biodiversity, 2023)
Abstract. Rohman F, Insani N, Purwanto, Dharmawan A, Fardhani I, Akhsani F. 2023. Short Communication: Vegetation and bird diversity in Pesanggrahan's lowland tropical forest, Malang, Indonesia. Biodiversitas 24: 6169-6176. Universitas Negeri Malang proposes the designation of Pesanggrahan Forest as a Forest Area with a Specific Purpose or Kawasan Hutan dengan Tujuan Khusus (KHDTK). This study investigated plant and bird communities in the lowland tropical forest of Pesanggrahan. We observed 31 tree species, with Teak being the most dominant, with a medium level of diversity (H': 1.67) and an uneven distribution (E: 0.48). There were 104 species of shrubs and forest floor plants with a high diversity (H': 3.45) and an even distribution (E: 0.74) and 49 bird species, with some being protected by the Regulation of the Ministry of Environment and Forestry and listed as